FINANCING EDUCATION IN UKRAINE IN THE CONDITIONS OF WAR AND RECONSTRUCTION (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Financing education is an important component of state policy, which contributes the formation of moral and spiritual values, knowledge and skills, and the development of qualified specialists, also plays an important role in the development of the state's economy. The war negatively affected on the material and technical base and financial support of education, which at the same time stimulates the need to find new approaches to its financing.Methods. The purpose is to identify problems in financing educational institutions and identify new approaches and sources of financial resources in the conditions of war and reconstruction.Purpose. The following methods and approaches were used to conduct research in the direction of education financing: the systematic approach ensured the identification of education financing problems in the context of the general socio-economic situation in the country, taking into account the impact of the war on education financing; a comparative approach was applied to enable the introduction of the experience of European Union countries in Ukraine to assess the effectiveness of financial models and identify best practices; the analysis method was applied using statistical data from the Ministry of Education and Science of Ukraine, the State Statistics Service to study the dynamics and trends of budget financing various types of educational institutions in Ukraine.Results. It has been studied that during the war, a large-scale redistribution of budgetary resources took place, and the structure and priorities of using funds from the state budget changed accordingly. During 2021–2024, the share of education expenditures in the state budget structure decreased from 4.28% in 2021 to 1.44% in 2024. In the structure of education expenditures, over 80% were expenditures on professional prehigher and higher education. In order to ensure equal access to quality education in different regions and  territorial communities, it is proposed to ensure efficiency of the distribution  educational subvention and create conditions for the expanding of public-private partnership.  Conclusions. Modernizing, reforming and changing of the education financing system is a strategic task for Ukraine, as diversification of financial resources will contribute to the implementation of innovative teaching methods and improve the quality of education. One of them could be attracting funds from private investors using the principles of public-private partnership.
Keywords: Financing education, state budget, public-private partnership, subvention, budget expenditures, financial standard of budgetary provision, decentralization, territorial community.